Pterins as diagnostic markers of exercise-induced stress: a systematic review - Lindsay, A.; Gieseg, S. P. (Journal of Science and Medicine in Sport, 2020)
Objectives: To evaluate pterins as diagnostic biomarkers of exercise-induced stress. Design: Systematic review of the literature. Methods: MEDLINE, Scopus and Web of Science were searched in March 2019 for relevant literature. We only considered in vivo studies of healthy humans that reported measurement of a pterin(s) in response to exercise or sport with no underlying prior disease or complication. Relevant articles were independently reviewed and resolved by consensus. Results: We included 29 studies with 644 participants. We classified articles by running/hiking, cycling, rugby, mixed martial arts (MMA) or other. Eighty-six percent of studies measured a significant increase in a pterin in response to exercise. Changes in pterin concentrations were within 24 h of the exercise-stimulus in 79% of studies and 17% measured a change from baseline greater than 48 h post-exercise (49% did not measure or report beyond 48 h). Neopterin or total neopterin (neopterin + 7,8-dihydroneopterin) were the primary pterin measured (28 studies) and they were equally sensitive to exercise regardless of whether the stimulus was running, cycling, rugby, MMA or other. Conclusions: Neopterin and total neopterin increase in response to exercise-induced stress. Pterins may have limited capacity for monitoring long-term stress beyond 48 h but further research is required.